Climate Change in Bangladesh : Confronting Impending Disasters. - Rasid, Harun (Lexington Books, 2013)
This book provides an essential interdisciplinary text on climate change and sea level rise in Bangladesh for undergraduate and graduate students of geography, environmental studies, sociology, anthropology, political science and others. Furthermore, it is an invaluable resource for managers and planners of the government of Bangladesh and several international agencies, including the United Nations, UNDP, UNEP, ADB, who are involved in climate change mitigation and adaptation.